A CRITIQUE OF THE MARXIST THEORY OF HISTORY FROM THE PERSPECTIVE OF THE AUSTRIAN SCHOOL OF ECONOMICS - Navarrete Callejero, Juan (REVISTA PROCESOS DE MERCADO, 2025)
This paper presents a comprehensive critique of the Marxist theory of history, focusing on a detailed analysis of the foundations of historical materialism and other key concepts from the perspective of the Austrian School of Economics. The study begins with an introduction highlighting Karl Marx’s remarkable influence on political and social thought, as well as the impact of his ideas on major events of the 20th century. It notes that, although widely accepted in certain academic and political circles, Marx’s theories had devastating consequences, directly contributing to the establishment of violent and totalitarian regimes that defined much of the last century’s history. The paper emphasizes how the application of Marxist tenets led to revolutions and the implementation of authoritarian systems, resulting in large-scale human tragedies. Throughout the work, the author aims to systematically dismantle Marx’s theory of history, adopting an approach similar to that used to critique his economic theory. Through a rigorous and in-depth analysis, the paper seeks to expose the internal contradictions and fallacies inherent in historical materialism, demonstrating how this theory not only falls short in explaining historical processes but has also served as an ideological justification for oppression and state control.